2013
DOI: 10.2174/157340013805289635
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunction in FMR1 Premutation Carriers

Abstract: Premutation carriers of the fragile X mental retardation gene (especially men) older than 50 may develop a neurodegenerative disease, the fragile X-associated tremor/ataxia syndrome (FXTAS). Carriers may present with varied cognitive impairments. Attention, working memory, declarative and procedural learning, information processing speed, and recall are among the cognitive domains affected. Executive dysfunction is a prominent deficit, which has been demonstrated mostly in men with FXTAS. In more advanced stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 73 publications
1
23
1
Order By: Relevance
“…These findings are in contrast to previous research using the same measure of memory function in larger samples Grigsby et al, 2008), where significant group differences in objective memory performance were observed when comparing PM males with and without FXTAS to controls. It is likely that the small number of PM males in the FXTAS group (n = 7) resulted in insufficient power to detect significant group effects in the current study, particularly given the inter-individual variability in cognitive features in PM males with FXTAS Seritan, Cogswell, & Grigsby, 2013;Seritan et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…These findings are in contrast to previous research using the same measure of memory function in larger samples Grigsby et al, 2008), where significant group differences in objective memory performance were observed when comparing PM males with and without FXTAS to controls. It is likely that the small number of PM males in the FXTAS group (n = 7) resulted in insufficient power to detect significant group effects in the current study, particularly given the inter-individual variability in cognitive features in PM males with FXTAS Seritan, Cogswell, & Grigsby, 2013;Seritan et al, 2008).…”
Section: Discussionmentioning
confidence: 92%
“…On the Mini Mental State Exam [9], a measure of general mental status, the difference in mean scores of FXTAS patients and controls was statistically, but not clinically, significant (27.6 vs 29.2). Nevertheless, a subset of individuals with FXTAS - most with advanced disease - demonstrates frank dementia [10,11]. Performance on measures of declarative memory is impaired, likely reflecting the effects of executive dysfunction (that is, problems with active learning and active retrieval) rather than a primary memory disorder.…”
Section: Reviewmentioning
confidence: 99%
“…This pattern of deficits indicates that FXTAS dementia is a mixed cortical-subcortical dementias, similarly to corticobasal degeneration and dementia with Lewy bodies, which also have parkinsonism as a prominent feature [65,71]. Due to the overlap of clinical signs and symptoms and the limited body of knowledge available to date, FXTAS dementia is difficult to distinguish from other dementias with movement disorders [71].…”
Section: Neuropsychiatric Phenotypes In Fxtasmentioning
confidence: 99%
“…Due to the overlap of clinical signs and symptoms and the limited body of knowledge available to date, FXTAS dementia is difficult to distinguish from other dementias with movement disorders [71]. FXTAS may be mistaken for Parkinson’s disease (PD) or spinocerebellar ataxia (SCA) in some cases, although studies have identified the FMR1 premutation in less than 1% of men clinically diagnosed with multiple system atrophy, PD or SCA [7274].…”
Section: Neuropsychiatric Phenotypes In Fxtasmentioning
confidence: 99%